2007
DOI: 10.1242/dev.02817
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy and specialization among plant microRNAs: role of theMIR164family in developmental robustness

Abstract: In plants, members of microRNA (miRNA) families are often predicted to target the same or overlapping sets of genes. It has thus been hypothesized that these miRNAs may act in a functionally redundant manner. This hypothesis is tested here by studying the effects of elimination of all three members of the MIR164 family from Arabidopsis. It was found that a loss of miR164 activity leads to a severe disruption of shoot development, in contrast to the effect of mutation in any single MIR164 gene. This indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
292
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(309 citation statements)
references
References 50 publications
16
292
1
Order By: Relevance
“…However, in other cases, miRNAs seem to be important for both spatially confining target mRNAs and for dampening their levels (McConnell et al, 2001;Kidner and Martienssen, 2004;Sieber et al, 2007). In se-1 and ago1-27 mutants as well as Pro35S:MIM156 plants, all of which have reduced miR156 activity, we observed a clear increase in the levels of the SPL9 target mRNA but no obvious expansion of its expression domain.…”
Section: Regulation Of Spl Expression By Mir156mentioning
confidence: 64%
“…However, in other cases, miRNAs seem to be important for both spatially confining target mRNAs and for dampening their levels (McConnell et al, 2001;Kidner and Martienssen, 2004;Sieber et al, 2007). In se-1 and ago1-27 mutants as well as Pro35S:MIM156 plants, all of which have reduced miR156 activity, we observed a clear increase in the levels of the SPL9 target mRNA but no obvious expansion of its expression domain.…”
Section: Regulation Of Spl Expression By Mir156mentioning
confidence: 64%
“…To investigate whether induction of growth repression in other domains of the leaf could be used to alter leaf shape, we created transgenic lines in which a modified form of KRP1 [KRP1miR164ts, in which the target sequence for miR164 (Nikovics et al, 2006) was spliced to the 3¢ end of the KRP1 coding sequence] could be inducibly expressed throughout the leaf (pOpON::KRP1miR164ts plants). The miRNA164 family has been shown to target cleavage of NAM/CUC transcripts in the shoot apex and developing leaves (Sieber et al, 2007;Raman et al, 2008). These studies also showed that the three Arabidopsis genes encoding miR164 (miR164a,b and c) are expressed in a complex fashion during early leaf development, including a phase during which miR164a is present in a domain that is essentially the same as that defined by the CUC2 promoter expression pattern ( Figure S1).…”
Section: Inhibition Of Growth In the Cuc2 Domain Leads To Leaf Lobingmentioning
confidence: 81%
“…Analysis of miR164 mutations and overexpression, as well as of miR164-insensitive CUC forms, has further revealed the importance of these genes for proper plant development [68][69][70]. A NAC-domain transcription factor encoded by the GOB gene is also a target gene in tomato.…”
Section: Transgenic Analysis In Exploring Mirnas Functionmentioning
confidence: 99%